Tight Integration and Synchronization of Distributed Graphical Applications - Müller, Wolfgang; Kleinjohann, Bernd (Proceedings of the Seventh Annual Database Symposium)

Approaching the Denotational Semantics of Behavioral VHDL Descriptions - Müller, Wolfgang (Proc. of the 1st Asian Pacific Conference on Hardware Description Languages, Standards and Applications)

Parallel Validation of STEP Files - Müller, Wolfgang; Lehrenfeld, Georg; Wiechers, N. (Proceedings of the 3nd EXPRESS User's Group Conference)

Kirchentag als vor-läufige Kirche. Der Kirchentag als eine besondere Gestalt des Christseins zwischen kirche und Welt - Schroeter-Wittke, Harald

Walter Benjamin und Bertolt Brecht - Ansätze zu einer dialektischen Ästhetik in den dreißiger Jahren. - Müller, Inez

Bibliographische Artikel zu Anastasius Grün (Anton Alexander Graf von Auersperg) Friedrich Halm (Eligius Franz Joseph Freiherr von Münch-Bellinghausen) und Friedrich von Sallet - Eke, Norbert Otto (Erstausgaben deutscher Dichtung. Eine Bibliographie zur deutschen Literatur 1600-1900)

Richard Wagner - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 12)

Alexander von Württemberg - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 12)

Simplifying Expressions Involving Radicals - Blömer, Johannes

Resemblance and symmetries of geometric patterns - Alt, Helmut; Blömer, Johannes (Data structures and efficient algorithms)

How to denest Ramanujan's nested radicals - Blömer, Johannes (Proceedings., 33rd Annual Symposium on Foundations of Computer Science)

Periodic Sorting on Two-Dimensional Meshes - Kutylowski, Miroslaw; Wanka, Rolf (Parallel Processing Letters 2)
We consider the following periodic sorting procedure on two-dimensional meshes of processors: Initially, each node contains one number. We proceed in rounds each round consisting of sorting the columns of the grid, and, in the second phase, of sorting the rows according to the snake-like ordering. We exactly characterize the number of rounds necessary to sort on an l × m-grid in the worst case, where l is the number of the rows and m the number of the columns. An upper bound of ⌈ log l⌉ + 1was known before. This bound is tight for the case that m is not a power of 2. Surprisingly, it turns out that far fewer rounds are necessary if m is a power of 2 (and m ≪ l) in this case, exactly min { log m + 1, ⌈ log l⌉ + 1} rounds are needed in the worst case.

Lenau-Chronik. „Und unterwegs erlahmen uns die Kräfte“ - Eke, Norbert Otto; Skrodzki, Karl Jürgen

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 6,2: Briefe 1838-1847. Teil 2: Anmerkungen (Edition) - Eke, Norbert Otto; Oellers, Norbert; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 5,2: Briefe 1812-1837. Teil 2: Anmerkungen (Edition) - Eke, Norbert Otto; Vizkelety, András; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Design and development of data visualization systems in a workstation environment - Domik, Gitta; Mickus-Miceli, Kristina D. (Journal of Microcomputer Applications)

Designing User-Centered Interfaces for Astrophysical Software - Domik, Gitta (Proceedings on User Interfaces for Astrophysical Software)

Functional Description of Parallel Processes - Koopman, Pieter; Groenewegen, Luuk; Engels, Gregor (Proceedings of the conference SION Computing Science in the Netherlands (CSN '92), The Netherlands)

Visual Specifications of Conceptual Database Schemata (Abstract) - Engels, Gregor

CADDY: A Highly Integrated Environment to Support Conceptual Database Design - Engels, Gregor; Löhr-Richter, Perdita (Proceedings of the Fifth International Workshop on Computer-Aided Software Engineering (CASE 1992), Montreal (Canada))
This experience report describes the development of the CASE environment CADDY Computer-Aided Design of non-traditional Databases 1 which oflers an integrated set of tools for specifying, analyzing, and prototyping a database application on a conceptual level. This environment was designed and implemented during the last four years at Braunschweig Technical University (Germany). The process of developing this environment consisted of a sequence of development steps, where each step corresponded to (at least) one of five main tasks. The intention of this report is to describe these five tasks. At the end, we will critically reflect on the achieved results and solved problems, but also on still open questions of the CADDY environment.

Specification of Coordinated Behaviour in the Software Development Process - Engels, Gregor; Groenewegen, Luuk (Proceedings of the Second European Workshop on Software Process Technology (EWSPT 92), Trondheim, Norway)

SQL/EER - Syntax and Semantics of an Entity-Relationship-Based Query Language - Hohenstein, Uwe; Engels, Gregor (Information Systems)
This paper presents the high-level query language SQL/EER for an extended Entity-Relationship model (EER model). SQL/EER directly supports all the concepts of the EER model and takes into account well-known features that are integral part of contemporary query languages, e.g. arithmetic and aggregate functions. In contrast to usual descriptions of query languages, we give SQL/EER a complete formal specification of syntax and sematics. This syntax is defined by using an attribute grammar which fixes the context-free structure and the context-sensitive rules. The operational semantics is defined by formally translating SQL/EER queries into queries of an existing, semantically well-defined calculus. The attribute grammar is extended to cover this translation, too. The query language SQL/EER is used in a database design environment. In this context, the formal specification of its syntax and the semantics has been used to implement a syntax-directed editor and a query interpreter for SQL/EER.

Building Integrated Software Development Environments, Part I: Tool Specification - Engels, Gregor; Lewerentz, Claus; Nagl, Manfred; Schäfer, Wilhelm; Schürr, Andy (ACM Transactions on Software Engineering and Methodology (TOSEM))
The conceptual modeling approach of the IPSEN (Integrated Project Support Environment) project for building highly integrated environments is based on using attributed graphs to model and implement arbitrary object structures, in particular all kinds of software documents and their relationships. A language based on graph grammars, called PROGRESS (Programmed Graph REwriting SyStems), and a suitable method for the application of this language, called graph grammar engineering, have been developed over the last ten years. This language and method are being extensively used for specifying the complex graph structures of internal document representations as well as for specifying the functionality of all tools (editors, browsers, analyzers, debuggers) working on these internal representations. This paper explains the language and the method for applying the language based on a pragmatic nontrivial example of a software production process and its corresponding documents. In particular, it is shown why and how a graph grammar-based strongly typed language is perfectly suitable to formally specify highly integrated software tools. In addition, it is shown that the implementation of these tools (i.e., an environment composed of these tools) is systematically being derived from the formal specifications.

Conceptual Modelling of Database Applications Using an Extended ER Model - Engels, Gregor; Gogolla, Martin; Hohenstein, Uwe; Hülsmann, Klaus; Löhr-Richter, Perdita; Saake, Gunter; Ehrich, Hans-Dietrich (Data & Knowledge Engineering)
In this paper, we motivate and present a data model for conceptual design of structural and behavioural aspects of databases. We follow an object centered design paradigm in the spirit of semantic data models. The specification of structural aspects is divided into modelling of object structures and modelling of data types used for describing object properties. The specification of object structures is based on an Extended Entity--Relationship (EER) model. The specification of behavioural aspects is divided into the modelling of admissible database state evolutions by means of temporal integrity constraints and the formulation of database (trans)actions. The central link for integrating these design components is a descriptive logic--based query language for the EER model. The logic part of this language is the basis for static constraints and descriptive action specifications by means of pre- and postconditions. A temporal extension of this logic is the specification language for temporal integrity constraints. We emphasize that the various aspects of a database application are specified using several appropriate, but yet compatible formalisms, which are integrated by a unifying common semantic.

Generic bifurcation of Hamiltonian vector fields with symmetry - Dellnitz, M; Melbourne, I; Marsden, J E (Nonlinearity)

High performance universal hashing, with applications to shared memory simulations - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Data structures and efficient algorithms)

Hashing strategies for simulating shared memory on distributed memory machines - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the performance of networks with multiple busses - Meyer auf der Heide, Friedhelm; Pham, Hieu Thien (STACS 92)

Efficient PRAM simulation on a distributed memory machine - Karp, Richard M.; Luby, Michael; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-fourth annual ACM symposium on Theory of computing - STOC '92)

Dynamic Hashing in Real Time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (TEUBNER-TEXTE zur Informatik)

Software design and development in a scientific environment: lessons learned during the development of STAR, an astrophysical analysis and visualization package - Domik, Gitta O; Mickus-Miceli, Kristina D (Astronomical Data Analysis Software and Systems I)

Visualization of Multi-dimensional Arrays in Astronomy - Domik, Gitta (European Southern Observatory Conference and Workshop Proceedings)

An Enriched Framework for Multidisciplinary Data Analysis - Mickus-Miceli, KD; Domik, G (Symposium on Intelligent Scientific Computation, American Association for Artificial Intelligence (AAAI), Fall 1992 Symposium Series, Cambridge MA, October)

Experimental Results to Interprocessor Communication in Distributed Transputer-Systems - Ginthör, Robert; Platzner, Marco; Weiss, Reinhold (Proceedings of the 1st Austrian-Hungarian Workshop on Transputer Applications)

The EXPRESS Information Modeling Workbench - A New Approach to Graphical Design Environments - Müller, Wolfgang; Kleinjohann, Bernd (Proceedings of the 2nd EXPRESS User's Group Conference)

„Wie wird künftig Meusel die hungrige Nachwelt hetzen und peinigen“. Deutsche Romane 1815-1830 in der Fürstlichen Bibliothek Corvey. Vorläufiges zum Forschungsprojekt „Der deutsche Roman 1815-1830" - Eke, Norbert Otto (Die Fürstliche Bibliothek Corvey. Ihre Bedeutung für eine neue Sicht der Literatur des frühen 19. Jahrhunderts. Beiträge des 1. Internationalen Corvey-Symposions. 25.-27. Oktober 1990 in Paderborn)

Diskussionsberichte zu den Sektionen 2 („Roman“) und 3 („Dramen“) sowie der Abschlußdiskussion des 1. Internationalen Corvey-Symposions - Eke, Norbert Otto (Die Fürstliche Bibliothek Corvey. Ihre Bedeutung für eine neue Sicht der Literatur des frühen 19. Jahrhunderts. Beiträge des 1. Internationalen Corvey-Symposions. 25.-27. Oktober 1990 in Paderborn)
Angaben zur Herausgeberschaft: Hg. von Rainer Schöwerling und Hartmut Steinecke unter Mitarbeit von Norbert Otto Eke und Günter Tiggesbäumker

Die Fürstliche Bibliothek Corvey. Ihre Bedeutung für eine neue Sicht der Literatur des frühen 19. Jahrhunderts. Beiträge des 1. Internationalen Corvey-Symposions. 25.-27. Oktober 1990 in Paderborn
Präzisierung der Herausgeberschaft: Hg. von Rainer Schöwerling und Hartmut Steinecke unter Mitarbeit von Norbert Otto Eke und Günter Tiggesbäumker

Georg von Reinbeck - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 9)

Friedrich von Sallet - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 10)

Matthias Leopold Schleifer - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 10)

Anton Xaver Schurz - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 10)

Herta Müller: Reisende auf einem Bein. Berlin 1989; Der Teufel sitzt im Spiegel. Wie Wahrnehmung sich erfindet. Berlin 1991 - Eke, Norbert Otto (Halbasien. Zeitschrift für deutsche Literatur und Kultur Südosteuropas)

Richard Wagner: Die Muren von Wien. Roman. Frankfurt/Main 1990 - Eke, Norbert Otto (Halbasien. Zeitschrift für deutsche Literatur und Kultur Südosteuropas)

ILFA Interface Concept - Dahn, Bernd I.; Lettmann, Theodor; Schönfeld, Wolfgang

Approximate matching of polygonal shapes (extended abstract) - Alt, Helmut; Behrends, Bernd; Blömer, Johannes (Proceedings of the seventh annual symposium on Computational geometry - SCG '91)

Computing sums of radicals in polynomial time - Blömer, Johannes (Proceedings 32nd Annual Symposium of Foundations of Computer Science)

Deutschsprachige Romane 1815-1830 in der Fürstlichen Bibliothek Corvey. Probleme der Erforschung – Bestandsverzeichnis - Eke, Norbert Otto; Steinecke, Hartmut; a., u.

Die erfundene Wahrnehmung. Annäherung an Herta Müller
2. Auflage: Hamburg 2009

Herta Müllers Werke im Spiegel der Kritik (1982-1990) - Eke, Norbert Otto (Die erfundene Wahrnehmung. Annäherung an Herta Müller)

„Überall, wo man den Tod gesehen hat“. Zeitlichkeit und Tod in der Prosa Herta Müllers - Eke, Norbert Otto (Die erfundene Wahrnehmung. Annäherung an Herta Müller)

Augen/Blicke oder: Die Wahrnehmung der Welt in den Bildern. Annäherung an Herta Müller - Eke, Norbert Otto (Die erfundene Wahrnehmung. Annäherung an Herta Müller)

„Der Neger schreibt ein andres Alphabet“. Anmerkungen zu Heiner Müllers dialektischem Denk-Spiel Anatomie Titus Fall of Rome. Ein Shakespearekommentar - Eke, Norbert Otto (Zeitschrift für deutsche Philologie)

Lenau und Graf Alexander von Württemberg oder: Der Dichter als (kritischer) Leser - Eke, Norbert Otto (Lenau-Forum)

Die deutschsprachige Literatur Osteuropas und ihre Rezeption in der Bundesrepublik. Probleme und Chancen einer 'kleinen Literatur' - Eke, Norbert Otto (Deutsche Studien 29)
Auch erschienen in: Neue Zeitung [Budapest], Nr 28 vom 14.7.1990, S. 6-7, und Nr 29 vom 21.7.1990, S. 8-9, sowie Neue Literatur [Bukarest], H. 5-6/1990/91, S. 22-42

The role of visualization in understanding data - Domik, Gitta (New Results and New Trends in Computer Science)

Incremental Design of Conceptual Database Schemata with CADDY - Löhr-Richter, Perdita; Engels, Gregor

Visualization in the Analysis Cycle of Observational Data, in Analyzing and Modeling Data and Knowledge - Domik, Gitta; Mickus, KD (Proceedings of the 15th Annual Conference of the "Gesellschaft für Klassifikation e.V." University of Salzburg)

Logic in Transition: The Logical Calculi of Hilbert (1905) and Zermelo (1908) [Abstract] - Peckhaus, Volker (Abstracts of the 9th International Congress of Logic, Methodology and Philosophy of Science, Uppsala, August 7–14, 1991, Bd. 2: General Philosophy of Science. Sections 6–9)

„Leich“ - Egidi, Margreth (Lexikon des Mittelalters, Bd. 5, Sp. 1850)

Contract-Oriented System Design and Specification - Müller, Wolfgang (Proceedings of the Workshop on Practical Computer Based Systems Engineering - its Scope and Methods)

Validation of EXPRESS Models Using Prolog - Lehrenfeld, Georg; Müller, Wolfgang (Proceedings of the 1st EXPRESS User's Group Conference)

Maximilian von Löwenthal - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 7)

Approximation of convex polygons - Alt, Helmut; Blömer, Johannes; Wagener, Hubert (Automata, Languages and Programming)

Hilbertprogramm und Kritische Philosophie. Das Göttinger Modell interdisziplinärer Zusammenarbeit zwischen Mathematik und Philosophie - Peckhaus, Volker
Anzeigen: Rundbrief der Philosophisch-Politischen Akademie e.V., Januar 1991); L'Enseignement Mathématique 37 (1991), Nr. 1–2 (Januar–Juni 1991), 5; Das gute Buch in der Schule 1991, Folge 3, 82. Abstract: Historia Mathematica 24 (1997), 230f., #24.2.141 (H.G. Steiner). Rezensionen: History and Philosophy of Logic 12 (1991), 246–247 (Ivor Grattan-Guinness) [zusammen mit M.-M. Toepell, Über die Entstehung von David Hilberts „Grundlagen der Geometrie“, Göttingen 1986]; Studia Logica 50 (1991), H. 2 (Juni 1991), 352–354 (Roman Murawski); Mathesis 7 (1991), 547-549 (J. Padilla Gálvez); Zbl. Math. 715 (Sept. 1991), #715.01018 (R. Rashed); Modern Logic 2 (1991/92), 196–199 (C. Smoryński); Deutsche Zeitschrift für Philosophie 40 (1992), H. 1/2, 191–195 (S. Gottwald); Deutsche Literaturzeitung 113 (1992), 306–308 (S. Paul); MR 92g:01054 (E. Mendelson); Anuario Filosofico 25 (1992), 435–436 (Carlos O. Landázuri); Jahresbericht der Deutschen Mathematiker-Vereinigung 94 (1992), H. 4 (Oktober 1992), 2. Abt., 55 (K. Jacobs); NTM. Schriftenreihe für Geschichte der Naturwissenschaften, Technik und Medizin 28 (1991/92), H. 2, 290 (R. Tobies); Isis 84 (1993), 823 (H. Mehrtens); Gerhard Heinzmann, « Métamathématique et philosophie », in: L'âge de la science, Bd. 5: Philosophie de la logique et philosophie du langage, Tl. 2, Édition Odile Jacob: Paris 1993, 169–177; Herbert Hrachovez, „Deutsche Positionen zur Informationstechnologie“, Philosophische Rundschau 41 (1994), 300– 314 (Sammelrezension, darin bes. 301–304); „Volker Peckhaus (1990): Los presupuestos intuicionistas del formalismo metamatemático de la Escuela de Gotinga a través de Hilbert“, Anuario Filosófico 30 (1997), Nr. 1, 296–297 (C. Ortiz de Landázuri); Anuario Filosófico 30 (1997), 741–742 (C. Ortiz de Landázuri); D. Rowe, “Perspectives on Hilbert”, Perspectives on Science 5 (1997), 533–570 (Sammelrezension, darin bes. 546– 553); Revue des Sciences philosophiques et théologiques 83 (1999), 141–143 (J. Courcier).

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 6,1: Briefe 1838-1847. Teil 1: Text (Edition) - Eke, Norbert Otto; Oellers, Norbert; Skrodzki, Karl Jürgen; Steinecke, Hartmut

„Niemand ist des anderen Sprache“. Zur deutschsprachigen Literatur Rumäniens - Eke, Norbert Otto (Südostdeutsche Vierteljahresblätter)

Radiokunst. Die Hörspiele Dieter Wellershoffs - Eke, Norbert Otto (Dieter Wellershoff)

Formal Semantics of an Entity-Relationship Query Language - Hohenstein, Uwe; Engels, Gregor (Proceedings of the 9th International Conference on Entity-Relationship Approach (ER 90), Lausanne, Switzerland)

The Influence of the Capsulation on the Efficiency of PV-Modules. - Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 1st World Renewable Energy Congress, Reading (UK), 23.–28. September 1990, Band 1, S. 141–144.)

Elementary Actions on an Extended Entity-Relationship Database - Engels, Gregor (Proceedings of the workshop on Graph Grammars and Their Application to Computer Science (1990), Bremen (Germany))
Semantic data models have been widely studied for the conceptual specification of databases. However, most of these data models are restricted to the description of the static structure of a database. They do not provide means to specify the dynamic behaviour of a database. This paper sketches a language for the specification of actions on databases which have been specified by an Extended Entity-Relationship (EER) schema. These actions are based on so-called elementary actions, which are automatically be derived from the EER schema. So, it can always be guaranteed that these schema dependent elementary actions preserve all inherent integrity constraints. The semantics of the elementary actions is given in two steps: First, it is shown how the semantics of a database schema, i.e., a current database state, can be represented by an attributed graph. Then, the semantics of elementary actions is given by programmed graph replacements.

A new universal class of hash functions and dynamic hashing in real time - Dietzfelbinger, Martin; Meyer auf der Heide, Friedhelm (Automata, Languages and Programming)

Dynamic hashing strategies - Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

On the complexity of genuinely polynomial computation - Karpinski, Marek; Meyer auf der Heide, Friedhelm (Lecture Notes in Computer Science)

How to distribute a dictionary in a complete network - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the twenty-second annual ACM symposium on Theory of computing - STOC '90)

Not all keys can be hashed in constant time - Gil, J.; Meyer auf der Heide, Friedhelm; Wigderson, A. (Proceedings of the twenty-second annual ACM symposium on Theory of computing - STOC '90)

Das Heinz Nixdorf-Institut der Universität-GH Paderborn - Meyer auf der Heide, Friedhelm (Informatik Spektrum)

IRAS On-Line Catalogs at CASA - Domik, Gitta; Brugel, E.W.; Stencel, R.E. (Proceedings of the 176th meeting of the American Astronomical Society)

Applications of IRAS Preprocessing at the Workstation - Domik, Gitta; Brugel, EW; Stencel, RE; Vasudevan, S; Pang, J (Bulletin of the American Astronomical Society)

Workstation-based preprocessing of IRAS sky-flux images - Domik, Gitta; Brugel, Edward W; Stencel, Robert E; Pang, Jinzhong; Vasudevan, Subramanian (Publications of the Astronomical Society of the Pacific)

A case study: Multi-sensor data analysis of hh objects via star: A scientific toolkit for astrophysical research - Mickus, KD; Brugel, EW; Domik, Gitta; Ayres, TR (Bulletin of the American Astronomical Society)

Star-a scientific toolkit for astrophysical research - Mickus, KD; Domik, Gitta; Brugel, EW; Ayres, TR (Bulletin of the American Astronomical Society)

Friedrich Halm - Eke, Norbert Otto (Literatur Lexikon. Autoren und Werke deutscher Sprache. Bd. 4)

Dieter Forte - Eke, Norbert Otto (Harenbergs Lexikon der Weltliteratur. Autoren – Werke – Begriffe. Bd. 2)

Herta Müller - Eke, Norbert Otto (Harenbergs Lexikon der Weltliteratur. Autoren – Werke – Begriffe. Bd. 4)

Norbert Mecklenburg: Erzählte Provinz. Regionalismus und Moderne im Roman. Königstein/Ts. 2. Auflage. 1986 - Eke, Norbert Otto (Germanistik. Internationales Referatenorgan mit bibliographischen Hinweisen)

Projections of vector addition system reachability sets are semilinear - Kleine Büning, Hans; Lettmann, Theodor; Mayr, Ernst W. (Theoretical Computer Science)

Heiner Müller. Apokalypse und Utopie - Eke, Norbert Otto

Nikolaus Lenau. Werke und Briefe. Historisch-kritische Gesamtausgabe. Bd. 5,1: Briefe 1812-1837. Teil 1: Text (Edition) - Eke, Norbert Otto; Vizkelety, András; Skrodzki, Karl Jürgen; Steinecke, Hartmut

Flankenspielorientierte Einstellung der Hypoid- und Kegelradgetriebe - Zimmer, Detmar

Konzepte einer Software-Architektur-Beschreibungssprache - Ebert, Jürgen; Engels, Gregor (Software-Entwicklung: Konzepte, Erfahrungen, Perspektiven, Fachtagung, 1989, Marburg (Germany))

CADDY-O: Syntaxgestütztes, graphisches Entwerfen konzeptioneller Datenbankschemata - Engels, Gregor (Tagungsband GI-Fachtagung "Interaktive Schnittstellen für Informationssysteme", TU Clausthal, Notizen zu Interaktive Systeme)

CADDY: Computer-Aided Design of Non-Standard Databases - Engels, Gregor; Hohenstein, Uwe; Hülsmann, Klaus; Löhr-Richter, Perdita; Ehrich, Hans-Dietrich (Proceedings of the International Conference on System Development Environments & Factories, Berlin, Germany)

Benutzerschnittstelle und Architektur der integrierten Datenbankentwurfsumgebung CADDY (Kurzfassung) - Engels, Gregor

Programmentwicklungsumgebungen: Konzepte und Realisierung - Engels, Gregor; Schäfer, Wilhelm

Computational methods for bifurcation problems with symmetries—with special attention to steady state and Hopf bifurcation points - Dellnitz, Michael; Werner, Bodo (Journal of Computational and Applied Mathematics)

On computations with integer division - Just, Bettina; Meyer auf der Heide, Friedhelm; Wigderson, Avi (RAIRO - Theoretical Informatics and Applications)

An optimal parallel dictionary - Dietzfelbinger, M.; Meyer auf der Heide, Friedhelm (Proceedings of the first annual ACM symposium on Parallel algorithms and architectures - SPAA '89)

On genuinely time bounded computations - Meyer auf der Heide, Friedhelm (STACS 89)

Time-optimal simulations of networks by universal parallel computers - Meyer auf der Heide, Friedhelm; Wanka, Rolf (STACS 89)